An investigation into the health status of the elderly population in China and the obstacles to achieving healthy aging - Haotian Wu; Yaqiang Wang; Han Zhang; Xiangjun Yin; Lijun Wang; Limin Wang; Jing Wu (Scientific Reports)
Abstract The phenomenon of population aging in China has evolved into an irreversible trend. The state places significant emphasis on the health-related initiatives for the elderly and has implemented pertinent policies. This study aims to identify the primary health issues affecting the elderly population in China, ascertain the key risk factors influencing their health, and offer a scientific foundation for the government to develop ongoing policies and strategies, as well as to allocate health resources efficiently. This study was conducted utilizing the nationwide surveillance and survey data collected by the National Center for Chronic and Noncommunicable Disease Control and Prevention, China. Descriptive statistics were employed to delineate the mortality rates, disease burden, prevalence of significant risk factors for chronic illnesses, as well as the incidence of disabilities and impairments among the elderly population in China. In 2019, the mortality rate of chronic non-communicable diseases among the elderly population in China aged 60 years and above was 31,238 per 100,000 individuals, representing 93.9% of all deaths. The disability-adjusted life years for males in the elderly population aged 60 years and above in 2019 totaled 103,850,000 person-years, while females accounted for 86,404,000 person-years. Among the elderly population in China, the top three diseases contributing to the highest Disability-Adjusted Life Years (DALYs) were stroke (19.202 million DALYs, representing 18.5% of the total DALYs), ischemic heart disease (13.895 million DALYs, 13.4%), and chronic obstructive pulmonary disease (COPD; 9.453 million DALYs, 9.1%). The primary risk factors associated with chronic diseases among the elderly population in China include inadequate consumption of fruits and vegetables, excessive intake of red meat, lack of physical activity, smoking, alcohol consumption, and being overweight or obese. There exist variations among genders, urban and rural areas, and regions. In 2015, the disability rate for activities of daily living (ADL) was notably high among the elderly population in China, reaching 19.4%. The prevalence of dysfunctions such as depressive symptoms, sleep disorders, and hearing loss is substantial. The prevalence of osteoporosis among the elderly in China is concerning. While China has achieved some progress in enhancing the health of the elderly, the current scenario of population aging in China is grave, and the health of the elderly continues to encounter numerous challenges. The prevalence of chronic diseases continues to be significant, with chronic conditions being the primary cause of mortality in the elderly population. Secondly, risk factors for chronic diseases persist among the elderly population, with a significant prevalence of smoking, alcohol consumption, and obesity. This issue is particularly serious in rural areas, showing an escalating trend that demands heightened attention. The prevalence of functional disorders among the elderly is notably high, and the issue of disability in this population segment is of significant concern. This study suggests five recommendations aimed at enhancing health-related policies and the health service system for the elderly, in response to the existing health challenges and demographic trends. The recommendations include creating an elderly-friendly environment, increasing government investment in elderly health, and addressing the aging population in China and so on to enhance the health outcomes of the elderly population in the country.